Views of patients on a group diabetic education programme using motivational interviewing in underserved communities in South Africa : qualitative study - Serfontein, Stephanus Johannes (Stellenbosch : Stellenbosch University, 2013)
Thesis (MFamMed)--Stellenbosch University, 2012.